2011
DOI: 10.1016/j.ajpath.2011.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Exposure of C57BL/6 Mice to Burkholderia pseudomallei Mimics Chronic Human Melioidosis

Abstract: Burkholderia pseudomallei is the etiological agent of human melioidosis, a disease with a broad spectrum of clinical manifestations ranging from fatal septicemia to chronic localized infection or asymptomatic latent infection. Most clinical and immunological studies to date have focused on the acute disease process; however, little is known about pathology and immune response in chronic melioidosis. Here, we have developed a murine model of chronic disease by challenging C57BL/6 mice intranasally with a low do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 51 publications
4
72
1
Order By: Relevance
“…with B. pseudomallei K96243 or the ⌬relA ⌬spoT double mutant at two different doses. A high dose of 2,500 CFU of B. pseudomallei K96243 has been shown to result in acute disease, with death of the mice occurring within 10 days postinfection, whereas a lower dose of Ͻ1,000 CFU results in a chronic infection (8). The ⌬relA ⌬spoT double mutant was attenuated in both the acute and the chronic model of infection, and all mice survived for at least up to 70 days postinfection (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…with B. pseudomallei K96243 or the ⌬relA ⌬spoT double mutant at two different doses. A high dose of 2,500 CFU of B. pseudomallei K96243 has been shown to result in acute disease, with death of the mice occurring within 10 days postinfection, whereas a lower dose of Ͻ1,000 CFU results in a chronic infection (8). The ⌬relA ⌬spoT double mutant was attenuated in both the acute and the chronic model of infection, and all mice survived for at least up to 70 days postinfection (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…challenge with 1 ϫ 10 2 CFU of wild-type B. pseudomallei (19). However, these studies were carried out in BALB/c mice, and we recently reported that the C57BL/6 infection model reflects the spectrum of melioidosis seen in humans (8). Therefore, we considered that the C57BL/6 infection model would allow a more meaningful assessment of the potential for live-attenuated mutants to induce protective immunity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Acute models, following either intravenous or the more physiologically relevant pulmonary route of B. pseudomallei infection, are characterized by the presence of bacteremia, neutrophil-dominant inflammation and uniformly rapid death (5, 8-10). We have also described a model of chronic melioidosis where granulomatous pathology, fibrosis and heterogeneity of disease progression are the main features within the infected animals (11). These models highlight the importance of neutrophil recruitment and IFNγ-mediated macrophage activation (12) in host resistance, but how B. pseudomallei resists elimination by these cell mediated immune responses is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model selection is critical given that licensure will ultimately require approval via the animal rule. The Balb/c and C57BL/6 murine models are considered to be reasonable small animal models of acute and chronic Burkholderia infection, 24,25 however, which is more representative of the human condition for initial vaccine testing remains unclear. Several large animal models are currently under investigation to include goats and multiple non-human primate species, 26,27 and continued investments in animal models to select that which most closely replicates the human condition is critical.…”
Section: Vaccines Against Viral Threatsmentioning
confidence: 99%